Analisis Penerapan Akuntansi Syariah Terhadap Pembiayaan Murabahah Berdasarkan PSAK No. 102 Pada PT. Bank BCA Syariah - Regita Azkia Putriadi; Wirman Wirman (Peneliti.net, 2022)
This study aims to determine the suitability of the application of murabahah financing accounting at PT. Bank BCA Syariah Bekasi Branch to Statement of Financial Accounting Standards Number 102 concerning Murabahah Accounting. This type of research is a qualitative descriptive research that describes and explains the application of the murabahah system in Islamic banking. The data sources used by the author are direct data sources (primary data) and indirect data sources (secondary data). The data collection technique in this study was field research, namely field data collection through documentation and interviews. In this research, the writer uses comparative analysis method. The comparative analysis method is a problem solving method or procedure that is studied by comparing the accounting applied to iB mortgage financing using a murabahah contract based on PSAK 102 at PT Bank BCA Syariah Bekasi Branch.